2012
DOI: 10.2298/aci1203089d
|View full text |Cite
|
Sign up to set email alerts
|

The effects of early rehabilitation in patients with surgically treated colorectal cancer

Abstract: Colorectal cancer is one of the most common cancer. Caught early, it is often curable. The important role in functional recovery of these patients, have enhanced recovery after surgery (ERAS) clinical care protocol and early rehabilitation. The goal of this research is the objective evaluation of the effects of early rehabilitation in patients after surgical treatment of colorectal cancer, respecting their functional recovery and quality of life, before and after rehabilitation. Tis study was made as experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These studies were conducted across breast (n=39), gynecologic 39-43 (n=5), colon and GI [44][45][46][47][48][49][50] (n=7), hematologic [51][52][53] (n=3), head and neck 54,55 (n=2), lung 56,57 (n=2), prostate 58,59 (n=2), and brain and CNS 60 (n=1) cancers, while 19 studies included various cancer diagnoses in their cohort [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] . A variety of cancer stages were represented across the studies, yet 34 studies did not specify stage of cancer for their cohort.…”
Section: Health-related Quality Of Life (Hrqol)mentioning
confidence: 99%
“…These studies were conducted across breast (n=39), gynecologic 39-43 (n=5), colon and GI [44][45][46][47][48][49][50] (n=7), hematologic [51][52][53] (n=3), head and neck 54,55 (n=2), lung 56,57 (n=2), prostate 58,59 (n=2), and brain and CNS 60 (n=1) cancers, while 19 studies included various cancer diagnoses in their cohort [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] . A variety of cancer stages were represented across the studies, yet 34 studies did not specify stage of cancer for their cohort.…”
Section: Health-related Quality Of Life (Hrqol)mentioning
confidence: 99%
“…20 In a study involving 58 patients with colorectal cancers, Djurasić et al found shorter hospital stays and improvements in functional postoperative recovery, quality of life, and physical and mental health with rehabilitation. 21 For women requiring surgery for breast cancer, postoperative rehabilitation has been shown to eliminate pain, restore shoulder mobility and strength and improve quality of life compared to controls. 22 Lymphedema is a chronic postoperative condition feared by many women who require lymph node biopsy.…”
Section: Rehabilitation To Improve Postoperative Functionmentioning
confidence: 99%